Effect of Foliar Spray of Kno3, Humic Acid Cultivars and Their Interactions on Leaf Nutrients of Olive (olea europaea l.) cvs. Khithary and i18 Transplants - Mayi, Azad A.; Saeed, Gulala M. A. (Science Journal of University of Zakho, 2015)
This study was carried out during the growing season (2012) in Bakrajo Nursery Station/ Sulaimani, Kurdistan Region-Iraq. Uniform and healthy olive (Olea europaea L.) cvs. Khithary and I 18 transplants of (2) years old were used. Filled with river loamy soil to investigate the effect of three levels KNO3 (0, 100 and 200 mg.L-1), three humic acid concentrations (0,150 and 300 mg.L-1) and their interactions on leaf nutrients of Olive cvs. Khithary and I 18 transplants. The results are summarizing as follows: Khithary significantly dominated over cv. I 18 in total leaf chlorophyll, P, K, Zn. However cv. I 18 significantly increased N and Fe. The interactions between cv. Khithary with KNO3 significantly increased P, K, Fe. While, cv. I 18 significantly increased N and Fe. The interactions between cv. I 18 +300ppm of humic acid significantly increased Fe. While Khithary with humic acid caused the highest values of N, P, K, Zn. The interactions between KNO3, humic acid and cv. Khithery affected significantly on most of the leaf nutrients characteristics. While, 200 ppm KNO3+0 humic acid with cv. Khithary increased all parameters except leaf Zn.